Propagation of Quantum Properties of Sub-Picosecond Solitons in a Fibre - Leuchs, Gerd; et al. (Optics Express, 1998)
We present new results on photon number squeezing of spectrally filtered solitons in fibers. The impact of frequency low-, high-, and bandpass filtering on noise reduction has been measured as a function of fiber length for 130-fs pulses close to the soliton energy. For short fibers our results agree qualitatively with theoretical predictions. For longer fibers, however, the measured squeezing increases to an unexpectedly large value. Spectral filtering of a strongly Raman-shifted, higher energy pulse squeezed the directly detected photocurrent fluctuations down to 3.8±0.2 dB (59%) below the shot noise level. The measured noise reductions are broadband from 5 to 90 MHz. © 1997 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.propag_4